Collaborative learning: A tried and true active learning method for the college classroom. (9th August 2022) - Major, Claire
Abstract: This chapter considers the essential elements of collaborative learning, reviews research supporting the efficacy of this instructional practice, and argues that students can be more or less active according to the structure of the collaborative task.